2016
DOI: 10.1016/j.jml.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Spoken word identification involves accessing position invariant phoneme representations

Abstract: Abstract:In two adaptation experiments we investigated the role of phonemes in speech perception. Participants repeatedly categorized an ambiguous test word that started with a blended /f/-/s/ fricative (?ail can be perceived as /fail/ or /sail/) or a blended /d/-/b/ stop (?ump can be perceived as /bump/ or /dump/) after exposure to a set of adaptor words. The adaptors all included unambiguous /f/ or /s/ fricatives, or alternatively, /d/ or /b/ stops. In Experiment 1 we manipulated the position of the adaptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 46 publications
2
39
1
Order By: Relevance
“…The previous data with voiceless fricatives, both from perceptual learning and selective adaptation (Bowers et al, 2016;Jesse & McQueen, 2011) are consistent with both hypotheses. Even in the perceptual-learning paradigm, there is generalization of learning across position for fricatives (Jesse & McQueen, 2011), and there is no moderation in terms of effect size in the amount of learning from codato-coda position to coda-to-onset position.…”
Section: Allophones In Spoken-word Recognition (In Press Journal Of supporting
confidence: 80%
See 4 more Smart Citations
“…The previous data with voiceless fricatives, both from perceptual learning and selective adaptation (Bowers et al, 2016;Jesse & McQueen, 2011) are consistent with both hypotheses. Even in the perceptual-learning paradigm, there is generalization of learning across position for fricatives (Jesse & McQueen, 2011), and there is no moderation in terms of effect size in the amount of learning from codato-coda position to coda-to-onset position.…”
Section: Allophones In Spoken-word Recognition (In Press Journal Of supporting
confidence: 80%
“…Importantly, data from a perceptual-learning paradigm showed that some form of prelexical unit has to be assumed to allow learning to generalize from one set of words to another (McQueen, Cutler, & Norris, 2006;Mitterer, Chen, & Zhou, 2011;Sjerps & McQueen, 2010). Regarding the size of the units, data using this perceptual-learning paradigm supports the hypothesis that there are allophonic units ALLOPHONES IN SPOKEN-WORD RECOGNITION (in press, Journal of Memory and Language) 3 (Mitterer, Scharenborg & McQueen, 2013), while data using a selective-adaptation paradigm supports the additional hypothesis that there are also phonemic units (Bowers, Kazanina, & Andermane, 2016). The present study tests these two representational hypotheses.…”
Section: Allophones In Spoken-word Recognition (In Press Journal Of mentioning
confidence: 67%
See 3 more Smart Citations